The Effect of Trust, Emotional Marketing, and Spiritual Marketing on Consumer Decisions To Choose Shopee Pay Digital Wallet Services - Isyana Rahayu; Didik Setiyadi (Business Review and Case Studies, 2022)
This study aims to analyze the relationship between trust, emotional marketing, and spiritual marketing through consumer decisions of digital wallets offered by Shopee pay. Digital wallets have been seen as a facility that provides convenience in transactions even though this technology also has risks, especially related to payments. Therefore, this study considers the factors of trust, emotional marketing, and spiritual marketing on consumer decisions to choose Shopee to pay digital wallets. This study uses a questionnaire for respondents as many as 82 people. This research is an explanatory study with analytical techniques using Smart PLS. The results show that emotional marketing affects consumer decisions in choosing a Shopee pay digital wallet. Meanwhile, trust and spiritual marketing have no significant effect on consumer decisions. Keywords: consumer decisions, emotional marketing, Shopee pay, spiritual marketing, trust